Migration histories and perfluoroalkyl acid (PFAA) loads in an estuarine fish: A novel union of analyses to understand variation in contaminant concentrations. (1st May 2021) - Taylor, Matthew D.; Gillanders, Bronwyn M.; Nilsson, Sandra; Bräunig, Jennifer; Barnes, Thomas C.; Mueller, Jochen F.
Abstract: Previous studies have shown that accumulation of perfluoroalkyl acids (PFAAs) in the tissues of aquatic species is highly variable. Movement and migration patterns in these species represent an important consideration when evaluating contaminant accumulation in exposed biota, and may have a large influence on the risk profiles for migratory seafood species. In this study, relationships between PFAA concentrations in muscle and liver tissue, and recent fish migration history (inferred from metals profiles in fish otoliths, otherwise known as otolith chemistry) were evaluated in Sea Mullet ( Mugil cephalus ). A greater number of PFAAs, and higher concentrations, were found in liver compared to muscle tissue. Perfluorooctane sulfonate (PFOS) was present in highest concentrations in both muscle and liver tissues, and there was strong correlation in concentrations between these two tissues. PFOS was found to decrease and increase alongside recent strontium and barium concentrations (respectively) in the otolith, suggesting higher concentrations of PFAAs in fish recently exposed to comparatively lower salinity environments. This study highlights how otolith chemistry can be employed to examine links between contaminant concentrations in fish, and their recent migration history. This approach shows promise for studying contaminant residues in mobile seafood species within the natural environment. Graphical abstract: Image 1 Highlights: A novel union of analyses is used to link fish migration to POP accumulation in fishes. Otolith chemistry was used to infer recent migration history of fish. Increased presence in brackish water correlated with increased PFAA concentrations. Otolith chemistry shows promise for understanding contaminant accumulation. Abstract : The results show that increasing association with brackish water, as identified using otolith chemistry, correlates with increased PFAA contamination.